Investigation of the use of forage species and non-forage multipurpose in systems of small and medium- producers of meat in the municipalities of Patía and Mercaderes, Cauca - Gutiérrez Solís, Jhon Freddy (2018)
The purpose is to evaluate forage germplasm with the potential use in the region, for which the establishment of genotype-environment tests (Multilocaciones) of some advanced and no evaluated forages materials in the region was performed in this case Cenchrus ciliaris and Chloris gayana, Under these evaluations, data were collected that allowed the selection of materials or accessions with better agronomic performance, taking into account variables such as; vigour, coverage, height, presence of pests and diseases, flowering, production of forage in terms of dry matter.